Sustainable water resources management of Prokletije region - Stevovic, Svetlana M; Milošević, Hranislav; Stevović, Ivan; Hadrović, Sabahudin (Industrija, 2014)
The main goal of this paper is the upgrading of classic economic analyses of optimal concept selection of small hydro development. Techno-economic small hydro system needs to be environmentally friendly and socially acceptable solution. Environmental and social parameters are quantified by Delphi method. They are results of Environmental and Social impact assessment study of the project. Environmental and social parameters are incorporated in the techno-economic analyses for the optimal sustainable concept of small hydro development, by Elektra method, as possible multi attributive operational research model. System of small hydro power plants optimization for Prokletije streams catchments area is case study where the developed model is tested and proofed. Economic cost and total investment of fifteen possible small hydro power plants has been upgraded with quantified environmental and social parameters and analyzed in the function of sustainable economic development of Prokletije region.